Fate of Electromagnetic Field on the Cracking of PSR J1614-2230 in Quadratic Regime - M. Azam; S. A. Mardan; M. A. Rehman (Advances in High Energy Physics)
We study the cracking of compact object PSR J1614-2230 in quadratic regime with electromagnetic field. For this purpose, we develop a general formalism to determine the cracking of charged compact objects. We apply local density perturbations to hydrostatic equilibrium equation as well as physical variables involved in the model. We plot the force distribution function against radius of the star with different parametric values of model both with and without charge. It is found that PSR J1614-2230 remains stable (no cracking) corresponding to different values of parameters when charge is zero, while it exhibits cracking (unstable) when charge is introduced. We conclude that stability region increases as amount of charge increases.